SOSIALISASI PENGEMBANGAN SOFT SKILL KEWIRAUSAHAAN PADA REMAJA DI DESA SALEM - Sari, Rinda Mayang; Adriansah, Adriansah (Universitas Bunda Mulia, 2022)
Soft skills or also known as skills are talents that can be developed in training without having to attend formal education. This expertise or skill becomes a basis for opening up opportunities for everyone in doing their business, especially for teenagers or young people who still have a productive age. Even during the ongoing COVID-19 pandemic, KPM the Islamic High School Community Service Program DR. KHEZ Muttaqien Purwakarta remains determined with a high spirit of inviting and educating young people to develop their skills so that they can earn money independently. Development of entrepreneurial soft skills so that they can encourage young people to be able to realize and develop abilities that are not possessed by others so that they can provide income from a young age. The targets of this program are teenagers or the younger generation in Salem Village, Pondoksalam District, who have not worked or do not have a job. The method used is socialization to each individual so that the understanding process can be absorbed according to the skills possessed by the teenager. The result of this program is that it can break down the skills or talents possessed by every teenager to become a businessman at a young age, so that it can help ease the burden on parents. In addition, this activity can create high enthusiasm to achieve what you want to aim for in the future without having to think about working in someone else's factory.